Transgenic poplar for resistance against pest and pathogen attack in forests: an overview - Swati Sharan; Amrita Chakraborty; Amit Roy; Indrakant K. Singh; Archana Singh; Archana Singh (Frontiers in Forests and Global Change)
Forests are potential habitats for immense terrestrial ecosystems and aquatic biodiversity, performing an essential role in ecological preservation and regulation of climate. The anthropogenic pressures on the forests lead to forest loss, fragmentation and degradation. Requirements for sustainable methodologies for forest protection are of utmost priority under the climate change regime. Among forest trees, poplar trees (Populus L.) have attracted attention in global forestry as a promising material for improving the quality and quantity of urban landscapes. These plants provide wood, which can be utilized as raw resources for the paper industry and as a potential source of biofuel. However, several biotic stresses, such as attacks by pests and pathogens, severely affect poplar production and productivity. The improvement of Populus trees through conventional tree breeding methods is restricted due to their long-life cycles and the lack of suitable donors with resistance genes. Populus has been utilized as a model plant for studying gene functions due to its highly efficient genetic transformation capabilities. The present review will provide a comprehensive overview of pest and pathogen attacks on poplar, focusing on their infection mechanisms, transmission routes, and control strategies. Additionally, it will examine the most widely used genetic transformation methods (gene gun-mediated, Agrobacterium tumefaciens-mediated, protoplast transformation, micro-RNA mediated and micro-RNA clustered regularly interspaced short palindromic repeats (CRISPR)-associated (CRISPR-Cas) systems methods and RNA interference) for improving tolerance in poplar trees against pest and pathogens attack. Furthermore, it will delve into prospects, challenges, and recent advances in molecular biology tools and their safe application for genetic transformation to improve insect and pest resistance in poplar trees. Finally, the regeneration of transgenic poplar trees with enhanced resistance, developed through various genetic engineering techniques, is discussed.